The Role of Kiai and Elder Teachers in the Formation of Islamic Civilization in Indonesia and Brunei - Deni Mahendra, Deden (Proceedings: International Seminar On Educational Studies, 2025)
Traditional Islamic education in the Malay–Nusantara region has played a significant historical role in shaping the Islamic civilization (Tamadun Islam) of Southeast Asia. Institutions such as pesantren in Indonesia and surau in Brunei have served not only as centers for religious education but also as social and cultural institutions that instill moral values and shape Muslim identity since the 17th century. This article aims to analyze the roles of the Kiai in Indonesia and the Guru Tua in Brunei in transmitting classical Islamic knowledge and inculcating the values of adab and akhlak through an educational approach based on ta’dib. The study shows that both Kiai and Guru Tua function as cultural and spiritual agents who maintain the continuity of Islamic traditions through a pedagogical system integrating knowledge, practice, and ethics. Traditional Islamic education in these regions emphasizes not only religious cognition but also the formation of civilized individuals in accordance with the concept of ta’dib, which lies at the heart of Islamic civilization. These findings affirm that pesantren and surau are strategic educational institutions in preserving Islamic values and strengthening the social cohesion of Malay–Nusantara Muslim societies in the modern era.